Solid waste based geopolymer and preparation method and application thereof

By mixing coal gasified slag, slag, red mud and calcium carbide slag in a specific proportion and adding water, using red mud and calcium carbide slag as strong alkaline exciters, we generate solid waste base polymers with high mechanical strength, solving the problem of ineffective utilization of solid waste, realizing the comprehensive utilization of solid waste and improving the strength of ground polymers.

CN119707332APending Publication Date: 2025-03-28CHINA ENERGY GRP NINGXIA COAL IND CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411729406.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, solid waste such as coal gasified slag and calcium carbide slag cannot be effectively utilized, resulting in waste of land resources and ecological environment pressure.

Method used

By mixing the gasified slag, slag, red mud and calcium carbide slag in a specific proportion, and adding appropriate amount of water to stir, a solid waste base polymer with high mechanical strength is generated. As strong alkaline excitants, red mud and calcium carbide slag stimulate the activity of slag and coal gasification slag, generate hydraulic gel-like substances such as hydrated calcium silicate and ettringite, and improve the strength of the polymer.

Benefits of technology

It has achieved effective comprehensive utilization of a variety of solid wastes, reduced solid waste emissions, improved the strength of ground polymers, reduced the consumption of chemical raw materials, reduced production costs, and has the advantages of environmental protection and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005159895390000081
    Figure BDA0005159895390000081
Patent Text Reader

Abstract

The invention provides a solid waste-based geopolymer as well as a preparation method and application thereof, the solid waste-based geopolymer comprises the following components: coal gasification slag, slag, red mud, carbide slag and sand, and the weight ratio of the coal gasification slag to the slag to the red mud to the carbide slag is (30-45): (30-45): (5-20): (5-20); the weight ratio of the sand to the sum of the weight of the coal gasification slag, the slag, the red mud and the carbide slag is (3-5): 1. The solid waste-based geopolymer disclosed by the invention has high strength, realizes effective comprehensive utilization of various solid wastes, and solves the problem that solid wastes such as coal gasification slag and carbide slag cannot be effectively utilized in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of building materials, and in particular to a solid waste-based polymer and a preparation method and application thereof. Background Art

[0002] Coal gasification slag is a byproduct of converting the effective components in coal into crude synthesis gas such as gasoline, diesel, ethers and alcohols. According to statistics, my country's coal gasification slag emissions exceed 60 million tons per year. Currently, it is mainly treated by storage and landfill, with an utilization rate of less than 50%. Red mud is a large amount of solid waste discharged during the production process of alumina industry. On average, 1.0-1.8 tons of red mud are produced for every 1.0 ton of alumina produced. my country's annual red mud production reaches 70 million tons. There is currently no effective large-scale utilization method, which has led to a serious waste of land resources and has caused tremendous pressure on the ecological environment. Therefore, how to effectively utilize the above solid waste to prepare geopolymers with high mechanical strength is of great significance. Summary of the invention

[0003] The main purpose of the present invention is to provide a solid waste-based polymer and a preparation method and application thereof, so as to solve the problem in the prior art that solid wastes such as coal gasification slag and carbide slag cannot be effectively utilized.

[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a solid waste-based polymer is provided, comprising the following components: coal gasification slag, slag, red mud, carbide slag and sand, the weight ratio of the coal gasification slag, slag, red mud and carbide slag is (25-35): (25-35): (10-25): (20-30); the weight ratio of sand to the sum of the weight of coal gasification slag, slag, red mud and carbide slag is (3-5): 1.

[0005] Furthermore, the weight ratio of coal gasification slag, slag, red mud and carbide slag is 30:30:15:25.

[0006] Furthermore, the particle size of the coal gasification slag is less than 0.03 mm.

[0007] Furthermore, the slag is S95 grade ore powder.

[0008] Furthermore, the red mud particle size is less than 200 mesh.

[0009] Furthermore, the particle size of the carbide slag is less than 200 mesh.

[0010] Furthermore, the sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of <3%.

[0011] Furthermore, the coal gasification slag is obtained by ball milling the coal gasification slag waste.

[0012] Furthermore, red mud is obtained by drying, grinding and sieving red mud waste in sequence.

[0013] Furthermore, carbide slag is prepared by the following steps: the carbide slag stock solution is allowed to stand for 5 to 7 days for stratification, and the precipitated layer is dried, ground, and sieved through a sieve in sequence to obtain red mud.

[0014] Furthermore, the initial water content of the carbide slag stock solution is not less than 90%.

[0015] Furthermore, the weight percentage content of calcium in the carbide slag is greater than 80% calculated as CaO.

[0016] According to another aspect of the present invention, a method for preparing a solid waste-based polymer is provided, comprising the following steps:

[0017] Step S1, mixing coal gasification slag, slag, red mud, carbide slag and sand to obtain a mixture;

[0018] Step S2, adding water to the mixture and stirring to obtain a solid waste-based polymer;

[0019] Among them, the weight ratio of coal gasification slag, slag, red mud and carbide slag is (30-45): (30-45): (5-20): (5-20); the weight ratio of sand to the sum of the weight of coal gasification slag, slag, red mud and carbide slag is (3-5): 1; the weight ratio of added water to solid waste base polymer is (0.12-0.15): 1.

[0020] According to another aspect of the present invention, there is provided use of the above solid waste-based polymer or the solid waste-based polymer prepared according to the above preparation method in road construction.

[0021] According to another aspect of the present invention, there is provided a roadbed material as above, comprising a hardened product of the solid waste-based polymer as above or the solid waste-based polymer prepared according to the preparation method as above;

[0022] Preferably, the solid waste-based polymer is loaded into a mold coated with a release agent and the mold is placed on a vibration table, the solid waste-based polymer is vibrated into shape, the molded solid waste-based polymer is cured for 20 to 30 hours and then demolded, and after demolding, it is cured for 7 to 28 days at a temperature of 18° C. to 22° C. and a relative humidity of 93% to 97% to obtain a hardened product.

[0023] By applying the technical solution of the present invention, the solid waste-based polymer uses solid waste coal gasification slag, slag, red mud, and carbide slag as raw materials, and uses the strong alkalinity of red mud and carbide slag to stimulate the slag and coal gasification slag matrix to generate hydration products with gelling properties, while using the high calcium content of red mud and carbide slag to improve the strength of the geopolymer. Among them, red mud contains calcium oxide and aluminum oxide, and its chemical components react with the components in solid waste coal gasification slag, slag and water to generate hydraulic gel-like substances such as calcium silicate hydrate (CSH) and calcium aluminate (AFt), thereby improving the strength of the geopolymer. Carbide slag is mainly composed of calcium carbide (CaC 2 ) is composed of the product after hydrolysis, and its chemical components mainly include calcium carbonate and calcium hydroxide. Its chemical components can react with the components in coal gasification slag, slag, red mud and water to form calcium silicate hydrate (CSH) and calcium aluminate (AFt), thereby improving the strength of the geopolymer and obtaining a high-strength geopolymer. At the same time, it realizes the effective comprehensive utilization of multiple solid wastes and reduces solid waste emissions. In addition, compared with traditional geopolymers using alkaline activators such as NaOH or water glass, the use of red mud and carbide slag as alkaline activators significantly reduces the consumption of chemical raw materials and can reduce production costs.

[0024] The solid waste-based polymer of the present invention has high strength and realizes the comprehensive utilization of solid waste, is beneficial to environmental protection, promotes the realization of the goal of sustainable development while reducing production costs, and has broad application prospects. DETAILED DESCRIPTION

[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0026] As described in the background art, there is a problem in the prior art that a large amount of coal gasification slag and carbide slag are continuously piled up over a large area and cannot be effectively and scaled up. In order to solve the above problem, according to one aspect of the present invention, a solid waste-based polymer is provided, comprising the following components: coal gasification slag, slag, red mud, carbide slag and sand, the weight ratio of coal gasification slag, slag, red mud and carbide slag is (25-35): (25-35): (10-25): (20-30); the weight ratio of sand to the sum of the weight of coal gasification slag, slag, red mud and carbide slag is (3-5): 1.

[0027] Coal gasification slag is a solid waste produced in the gasification process of coal-to-liquid, and has certain volcanic ash activity. Slag is an industrial waste produced in the process of steel production, mainly containing minerals such as silicates, aluminates and calcium oxide, which can provide a stable source of silicate aluminates for the geopolymerization process. Red mud is a large amount of solid waste discharged in the production process of alumina industry. Solid waste base polymer uses solid waste coal gasification slag, slag, red mud, and carbide slag as raw materials. The strong alkalinity of red mud and carbide slag is used to stimulate the slag and coal gasification slag matrix to generate hydration products with gelling properties, and the high calcium content of red mud and carbide slag is used to improve the strength of geopolymer. Among them, red mud contains calcium oxide and aluminum oxide, and its chemical components react with the components in solid waste coal gasification slag, slag and water to generate hydraulic gel-like substances such as calcium silicate hydrate (CSH) and calcium aluminate (AFt), thereby improving the strength of geopolymer. Red mud also contains active SiO 2 And a certain amount of Na 2 O, which has potential volcanic ash activity and alkalinity, can provide a certain alkaline environment and amorphous silicon-aluminum components, thereby improving the strength of the solid waste base polymer; red mud also contains a large number of crystals, which do not participate in the reaction during the geopolymer reaction, and their presence can also improve the strength of the geopolymer. Carbide slag is mainly composed of calcium carbide (CaC 2 ) after hydrolysis, its chemical components mainly include calcium carbonate and calcium hydroxide, and its chemical components can react with the components in coal gasification slag, slag, red mud and water to generate hydrated calcium silicate (CSH) and calcium aluminate (AFt), thereby improving the strength of the geopolymer and obtaining a high-strength geopolymer, and at the same time achieving effective comprehensive utilization of a variety of solid wastes and reducing solid waste emissions; in addition, compared with the traditional geopolymer using alkaline activators such as NaOH or water glass, the use of red mud and carbide slag as alkaline activators significantly reduces the consumption of chemical raw materials and can reduce production costs. The solid waste-based polymer based on the present invention has high strength and realizes the comprehensive utilization of solid waste, is beneficial to environmental protection, and promotes the realization of the goal of sustainable development while reducing production costs, and has broad application prospects.

[0028] In some embodiments, the weight ratio of coal gasification slag, slag, red mud and carbide slag is 30:30:15:2. The solid waste-based polymer obtained under the above weight ratio has better strength and stability, can be better applied in the construction field, reduces solid waste emissions, and is conducive to environmental remediation and soil quality improvement.

[0029] In some embodiments, the particle size of the coal gasification slag is less than 0.03 mm, which is beneficial to improving the uniformity of the coal gasification slag, obtaining a higher strength solid waste-based polymer product, and improving the production efficiency of the product.

[0030] In some embodiments, in order to obtain a higher strength solid waste-based polymer product, the slag is S95 grade mineral powder.

[0031] In some embodiments, in order to obtain higher strength solid waste-based polymer products, the red mud particle size is less than 200 mesh.

[0032] In some embodiments, in order to obtain higher strength solid waste-based polymer products, the particle size of the carbide slag is less than 200 mesh.

[0033] In some embodiments, in order to obtain a higher strength solid waste-based polymer product, the sand is gangue sand with a particle size of less than or equal to 2.36 mm and a mud content of <3%.

[0034] In some embodiments, the coal gasification slag is obtained by ball milling coal gasification slag waste, which has high production efficiency and is suitable for large-scale production.

[0035] In some embodiments, red mud is obtained by sequentially drying, grinding, and sieving red mud waste, which is conducive to obtaining powdered carbide slag with good dispersibility and uniform particle size.

[0036] In some embodiments, carbide slag is prepared by the following steps: standing carbide slag stock solution for 5 to 7 days for stratification, taking the precipitate layer and drying, grinding, and sieving through a sieve in sequence to obtain red mud. The above process is used to treat carbide slag stock solution to obtain red mud, which has a simple process and a high red mud recovery rate.

[0037] In some embodiments, the initial water content of the carbide slag raw liquid is not less than 90%.

[0038] In some embodiments, the weight percentage content of calcium in carbide slag is greater than 80% in terms of CaO. The high content of calcium oxide makes carbide slag highly alkaline and can react with a variety of substances, which is beneficial to improving the mechanical properties of solid waste-based polymers. For example, the high content of calcium oxide in carbide slag is beneficial to stimulate the activity of slag and improve the mechanical strength of geopolymers. The high calcium oxide in carbide slag can react with the active ingredients in red mud to generate gel-like substances such as hydrated calcium silicate, thereby improving the strength and durability of geopolymers.

[0039] According to another aspect of the present invention, a method for preparing a solid waste-based polymer is provided, comprising the following steps:

[0040] Step S1, mixing coal gasification slag, slag, red mud, carbide slag and sand to obtain a mixture;

[0041] Step S2, adding water to the mixture and stirring to obtain a solid waste-based polymer;

[0042] Among them, the weight ratio of coal gasification slag, slag, red mud and carbide slag is (30-45): (30-45): (5-20): (5-20); the weight ratio of sand to the sum of the weight of coal gasification slag, slag, red mud and carbide slag is (3-5): 1; the weight ratio of added water to solid waste base polymer is (0.12-0.15): 1.

[0043] According to another aspect of the present invention, there is provided an application of the solid waste-based polymer as described above or the solid waste-based polymer prepared according to the preparation method as described above in the field of road construction. Exemplarily, it is used for supporting and reinforcing underground spaces in roads.

[0044] According to another aspect of the present invention, there is provided a roadbed material as described above, comprising a hardened product of the solid waste-based polymer as described above or the solid waste-based polymer prepared according to the preparation method as described above.

[0045] In one embodiment, a solid waste-based polymer is loaded into a mold coated with a release agent and the mold is placed on a vibration table to vibrate the solid waste-based polymer into shape. The molded solid waste-based polymer is demolded after curing for 20 to 30 hours. After demolding, the solid waste-based polymer is cured for 7 to 28 days at a temperature of 18° C. to 22° C. and a relative humidity of 93% to 97% to obtain a hardened product.

[0046] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0047] Unless otherwise specified, the raw materials and reagents used in the examples and comparative examples were purchased from the market.

[0048] Example 1

[0049] A solid waste-based polymer comprises the following components: coal gasification slag, slag, red mud, carbide slag (calculated as CaO, the weight percentage content of calcium in the carbide slag is 88.30%) and sand, wherein the weight ratio of the coal gasification slag, slag, red mud and carbide slag is 30:30:15:25; the weight ratio of sand to the sum of the weight of the coal gasification slag, slag, red mud and carbide slag is 5:1;

[0050] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0051] The slag is S95 grade ore powder;

[0052] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0053] The red mud is obtained by drying, grinding and sieving red mud waste through a 200-mesh sieve in sequence;

[0054] The carbide slag is prepared by the following steps: the carbide slag stock solution is allowed to stand for 6 days for stratification, and the precipitated layer is dried, ground, and sieved through a 200-mesh sieve to obtain red mud.

[0055] The steps for preparing solid waste-based polymers are as follows:

[0056] Step 1: add 0.12 kg of coal gasification slag, 0.12 kg of slag, 0.06 kg of red mud, 0.1 kg of carbide slag and 2.0 kg of sand into a forced mixer in sequence and mix well to obtain a mixture;

[0057] Step 2: Add 0.391 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0058] Example 2

[0059] A solid waste-based polymer comprises the following components: coal gasification slag, slag, red mud, carbide slag (calculated as CaO, the weight percentage content of calcium in the carbide slag is 88.30%) and sand, wherein the weight ratio of the coal gasification slag, slag, red mud and carbide slag is 30:30:15:25; the weight ratio of sand to the sum of the weight of the coal gasification slag, slag, red mud and carbide slag is 4:1;

[0060] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0061] The slag is S95 grade ore powder;

[0062] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0063] The red mud is obtained by drying, grinding and sieving red mud waste through a 200-mesh sieve in sequence;

[0064] The carbide slag is prepared by the following steps: the carbide slag stock solution is allowed to stand for 6 days for stratification, and the precipitated layer is dried, ground, and sieved through a 200-mesh sieve to obtain red mud.

[0065] The steps for preparing solid waste-based polymers are as follows:

[0066] Step 1: add 0.15 kg of coal gasification slag, 0.155 kg of slag, 0.075 kg of red mud, 0.12 kg of calcium carbide slag and 2.0 kg of calcium carbide slag into a forced mixer in sequence and mix well to obtain a mixture;

[0067] Step 2: Add 0.407 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0068] Example 3

[0069] A solid waste-based polymer comprises the following components: coal gasification slag, slag, red mud, carbide slag (calculated as CaO, the weight percentage content of calcium in the carbide slag is 88.30%) and sand, wherein the weight ratio of the coal gasification slag, slag, red mud and carbide slag is 30:30:15:25; the weight ratio of sand to the sum of the weight of the coal gasification slag, slag, red mud and carbide slag is 3:1;

[0070] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0071] The slag is S95 grade ore powder;

[0072] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0073] The red mud is obtained by drying, grinding and sieving red mud waste through a 200-mesh sieve in sequence;

[0074] The carbide slag is prepared by the following steps: the carbide slag stock solution is allowed to stand for 6 days for stratification, and the precipitated layer is dried, ground, and sieved through a 200-mesh sieve to obtain red mud.

[0075] The steps for preparing solid waste-based polymers are as follows:

[0076] Step 1, add 0.20kg of coal gasification slag, 0.20kg of slag, 0.10kg of red mud, 0.167kg of carbide slag, and 2.0kg of carbide slag into a forced mixer in sequence and stir evenly to obtain a mixture;

[0077] Step 2: Add 0.435 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0078] Comparative Example 1

[0079] The only difference from Example 1 is that the weight ratio of sand to the sum of the weight of coal gasification slag, slag, red mud and carbide slag is 6:1, as follows:

[0080] A solid waste-based polymer comprises the following components: coal gasification slag, slag, red mud, carbide slag and sand, wherein the weight ratio of the coal gasification slag, slag, red mud and carbide slag is 30:30:15:25; the weight ratio of sand to the sum of the weight of the coal gasification slag, slag, red mud and carbide slag is 6:1;

[0081] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0082] The slag is S95 grade ore powder;

[0083] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0084] The red mud is obtained by drying, grinding and sieving red mud waste through a 200-mesh sieve in sequence;

[0085] The carbide slag is prepared by the following steps: the carbide slag stock solution is allowed to stand for 6 days for stratification, and the precipitated layer is dried, ground, and sieved through a 200-mesh sieve to obtain red mud.

[0086] The steps for preparing solid waste-based polymers are as follows:

[0087] Step 1: add 0.1 kg of coal gasification slag, 0.1 kg of slag, 0.05 kg of red mud, 0.083 kg of carbide slag and 2.0 kg of sand into a forced mixer in sequence and mix well to obtain a mixture;

[0088] Step 2: Add 0.3798 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0089] Comparative Example 2

[0090] The only difference from Example 1 is that the carbide slag is replaced with red mud of equal mass, as follows:

[0091] A solid waste-based polymer comprises the following components: coal gasification slag, slag, red mud and sand, wherein the weight ratio of the coal gasification slag, slag, red mud and carbide slag is 30:30:40; the weight ratio of sand to the sum of the weight of the coal gasification slag, slag and red mud is 5:1;

[0092] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0093] The slag is S95 grade ore powder;

[0094] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0095] The red mud is obtained by drying, grinding and sieving red mud waste through a 200-mesh sieve in sequence;

[0096] The steps for preparing solid waste-based polymers are as follows:

[0097] Step 1: add 0.12 kg of coal gasification slag, 0.12 kg of slag, 0.16 kg of red mud and 2.0 kg of sand into a forced mixer in sequence and mix them evenly to obtain a mixture;

[0098] Step 2: Add 0.391 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0099] Comparative Example 3

[0100] The difference between the embodiment and the embodiment is that the red mud is replaced by carbide slag of equal mass, as follows:

[0101] A solid waste-based polymer comprises the following components: coal gasification slag, slag, carbide slag and sand, wherein the weight ratio of the coal gasification slag, slag, red mud and carbide slag is 30:30:15:25; the weight ratio of sand to the sum of the weight of the coal gasification slag, slag and carbide slag is 5:1;

[0102] The coal gasification slag is obtained by ball milling the coal gasification slag waste for 80 minutes, and the particle size is less than 0.03 mm;

[0103] The slag is S95 grade ore powder;

[0104] The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%;

[0105] The carbide slag is prepared by the following steps: the carbide slag stock solution is allowed to stand for 6 days for stratification, and the precipitated layer is dried, ground, and sieved through a 200-mesh sieve to obtain red mud.

[0106] The steps for preparing solid waste-based polymers are as follows:

[0107] Step 1: add 0.12 kg of coal gasification slag, 0.12 kg of slag, 0.16 kg of carbide slag and 2.0 kg of sand into a forced mixer in sequence and mix them evenly to obtain a mixture;

[0108] Step 2: Add 0.391 kg of mixed water to the mixture and stir evenly to obtain a solid waste-based polymer.

[0109] The performance tests of the solid waste-based polymers prepared in Examples 1-3 were performed:

[0110] (1) The solid waste-based polymer is placed in a mold coated with a release agent and pounded evenly. After pounding evenly, the mold is placed on a vibration table to vibrate the solid waste-based polymer into shape. The molded solid waste-based polymer is cured for 24 hours and then demolded. After demolding, it is cured for 3 days, 7 days, 14 days, and 28 days at a temperature of 20±0.5°C and a relative humidity of 95±2%, respectively, to obtain a series of hardened products.

[0111] (2) The compressive strength of the hardened products was tested after different curing days. The test results are shown in Table 1.

[0112] Table 1

[0113]

[0114] Compared with Comparative Examples 1-3, the material strength of the hardened products prepared using the solid waste-based polymers in Examples 1-3 is significantly increased.

[0115] It can be seen from Example 1, Example 2, Example 3 and Comparative Example 1 that when the ratio of sand material to cementitious material is reduced from 6:1 to 3:1, the strength of the hardened product material increases. As the content of cementitious material increases, the hydration products increase and the bonding force between particles increases, thereby improving the strength of the geopolymer.

[0116] From the comparison of Example 1 and Comparative Example 2, it can be seen that only adding the alkaline activator red mud will cause the strength of the hardened product prepared by the geopolymer to decrease significantly. As an alkaline activator, carbide slag can more effectively stimulate the activity of industrial solid wastes such as coal gasification slag and slag, promote hydration reaction, and generate gel-like substances such as hydrated calcium silicate (CSH), thereby improving the strength and durability of the geopolymer. In addition, by generating hydration products such as calcium aluminate, carbide slag can improve the pore structure of the geopolymer, reduce the porosity, and improve the density and compressive strength of the material. Compared with carbide slag, the alkali activation activity of red mud is lower. It is difficult to effectively activate solid waste coal gasification slag, slag, etc. by adding only red mud, resulting in insufficient hydration reaction and a reduction in the generated hydration products, thereby affecting the strength of the geopolymer. From Example 1 and Comparative Example 3, it can be seen that only adding the alkaline activator carbide slag will cause the strength of the hardened product prepared by the geopolymer to decrease significantly. In addition to calcium oxide and aluminum oxide, red mud also contains active SiO 2 And a certain amount of Na 2 O, which has both potential volcanic ash activity and alkalinity, can provide a certain alkaline environment and amorphous silicon-aluminum components, thereby improving the strength of solid waste base polymers; in addition, red mud contains a large number of crystals, which do not participate in the reaction during the geopolymer reaction, and their presence can also improve the strength of geopolymers. It can be seen that red mud and carbide slag, as alkaline activators, can effectively improve the strength of geopolymers by adding them and coordinating the ratio of various raw materials, and realize the comprehensive utilization of various solid wastes.

[0117] As shown in Table 1, after 7 days of curing, the strength of the hardened product material reached more than 3MPa, which is significantly higher than the minimum strength requirement of 2MPa for underground filling materials in my country, and can be used to support and reinforce underground spaces in roads. The products prepared based on the solid waste-based polymer of the present invention have high strength and realize the comprehensive utilization of solid waste, which is beneficial to environmental protection, reduces production costs and promotes the realization of sustainable development goals, and has broad application prospects.

[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A solid waste-based polymer, characterized in that: The invention comprises the following components: coal gasification slag, slag, red mud, carbide slag and sand, wherein the weight ratio of the coal gasification slag, the slag, the red mud and the carbide slag is (25-35): (25-35): (10-25): (20-30); the weight ratio of the sand to the sum of the weight of the coal gasification slag, the slag, the red mud and the carbide slag is (3-5):

1.

2. The solid waste-based polymer according to claim 1, characterized in that: The weight ratio of the coal gasification slag, the slag, the red mud and the carbide slag is 30:30:15:

25.

3. The solid waste-based polymer according to claim 1 or 2, characterized in that: The particle size of the coal gasification slag is less than 0.03 mm; and / or, The slag is S95 grade slag powder; and / or, The red mud particle size is less than 200 mesh; The particle size of the carbide slag is less than 200 mesh; and / or, The sand is gangue sand, with a particle size of less than or equal to 2.36 mm and a mud content of less than 3%.

4. The solid waste-based polymer according to claim 1 or 2, characterized in that: The coal gasification slag is obtained by ball milling coal gasification slag waste; and / or The red mud is obtained by sequentially drying, grinding and screening red mud waste.

5. The solid waste-based polymer according to claim 1 or 2, characterized in that: The carbide slag is prepared by the following steps: The carbide slag stock solution is allowed to stand for 5 to 7 days to be layered, and the precipitated layer is dried, ground, and sieved through a sieve in sequence to obtain the red mud.

6. The solid waste-based polymer according to claim 5, characterized in that: The initial water content of the carbide slag stock solution is not less than 90%.

7. The solid waste-based polymer according to claim 1 or 2, characterized in that: Calculated as CaO, the weight percentage content of calcium in the carbide slag is greater than 80%.

8. A method for preparing a solid waste-based polymer, characterized in that: The steps include: Step S1, mixing coal gasification slag, slag, red mud, carbide slag and sand to obtain a mixture; Step S2, adding water to the mixture and stirring to obtain the solid waste-based polymer; Wherein, the weight ratio of the coal gasification slag, the slag, the red mud and the carbide slag is (30-45): (30~45):(5~20):(5~20); the weight ratio of the sand to the sum of the weight of the coal gasification slag, the slag, the red mud and the carbide slag is (3~5):1; the weight ratio of the added water to the solid waste-based polymer is (0.12~0.15):

1.

9. Use of the solid waste-based polymer according to any one of claims 1 to 7 or the solid waste-based polymer prepared by the preparation method according to claim 8 in road construction.

10. A roadbed material, characterized in that: A hardened product comprising a solid waste-based polymer according to any one of claims 1 to 7 or a solid waste-based polymer prepared by the preparation method according to claim 8; Preferably, the solid waste-based polymer is loaded into a mold coated with a release agent and the mold is placed on a vibration table, the solid waste-based polymer is vibrated to form, the molded solid waste-based polymer is demolded after curing for 20 to 30 hours, and after demolding, it is cured for 7 to 28 days at a temperature of 18° C. to 22° C. and a relative humidity of 93% to 97% to obtain the hardened product.